Prevalence of ocular disorders in Liberia: a retrospective study using the eyeSmart electronic medical record system - Anthony Vipin Das; Priyanka Kammari; Edward Bea Guizie; Rajashekar Varada; Gurcharan Singh (Journal of Global Health Reports, 2019)
# Background